Tinjauan Terhadap Dampak Negatif Legalisasi Narkoba di Indonesia - Andy Winardi; Shannon Gandrova; Albert Lodewyk Siahaan (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Narcotics (narcotics and dangerous drugs) are addictive substances that damage the nervous system and have psychological impacts such as hallucinations and addiction, and have negative impacts on health. Drug use is not only limited to the drug tablets consumed, but can also be items that are inhaled, smoked, swallowed or injected. Law No. 35 of 2009 concerning Narcotics Article 1 paragraph 1 states that narcotics are artificial substances or those originating from plants that have hallucinatory effects, reduce consciousness, and cause addiction. Even though it was intended for positive purposes, it was gradually realized that the use of drugs in large doses actually had negative effects on the users. The dangers of drug use are the reason for the Indonesian state to prohibit the legalization of drugs. Reporting from a BNN survey, it is known that there are around 4.8 million people in the 15-64 year age range who have used drugs in 2022-2023. Apart from that, the Deputy Minister of Law and Human Rights also explained that 59.4% of prison inmates were drug offenders. Narcotics are seen as an extraordinary crime and Indonesia strongly opposes the legalization of drugs. In efforts to eradicate drugs, Indonesia has 3 laws regarding narcotics, namely Law no. 9 of 1976, Law no. 22 of 1997 and Law no. 35 of 2009, all of which contains prohibitions on the production, use, distribution, sale and possession of narcotics.